13th International Ceramics Congress : proceedings of the 13th International Ceramics Congress, part of CIMTEC 2014-13th International Ceramics Congress and 6th Forum on New Materials, June 8-13, 2014, Montecatini Terme, Italy. Part A - Vincenzini, P., 1939-; Yoshimura, Masahiro (Advances in science and technology (Faenza, Italy) ;, 2014)
Collection of selected, peer reviewed papers from the 13 th International Ceramics Congress, part of CIMTEC 2014-13 th International Ceramics Congress and 6 th Forum on New Materials, June 8-13, 2014, Montecatini Terme, Italy. The 27 papers are grouped as follows: Chapter 1: Powder Synthesis and Characterization, Chapter 2: Colloidal Processing, Shape Forming and Compaction Mechanisms, Chapter 3: Sintering and Related Phenomena. Temporary description, more details to follow.